Dipta Apparels Limited (DIRD Group): Production, HRM & Compliance, IE, Merchandising and Commercial - Sultan, Tipu (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.